Further properties and a fast realization of the iterative truncated arithmetic mean filter - Miao, Zhenwei (2013)
The iterative truncated arithmetic mean (ITM) filter has been recently proposed. It possesses merits of both the mean and median filters. In this brief, the Cramer-Rao lower bound is employed to further analyze the ITM filter. It shows that this filter outperforms the median filter in attenuating not only the short-tailed Gaussian noise but also the long-tailed Laplacian noise. A fast realization of the ITM filter is proposed. Its computational complexity is studied. Experimental results demonstrate that the proposed algorithm is faster than the standard median filter.